2015
DOI: 10.1007/s00394-015-1082-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B2, vitamin B12 and total homocysteine status in children and their associations with dietary intake of B-vitamins from different food groups: the Healthy Growth Study

Abstract: A considerably high prevalence of poor plasma vitamin B status was observed in children. The intake of milk, fruits and cereals was associated with more favorable tHcy levels, while the intake of milk and fruits with more favorable plasma B2 levels. However, these findings need to be further confirmed from controlled dietary intervention studies examining the modulation of biomarkers of B-vitamins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 35 publications
1
22
0
1
Order By: Relevance
“…The important role of dairy in ensuring nutrient intake adequacy and sufficient concentrations of nutrient status blood indices was recently reported for the population of schoolchildren examined in the present study [2,6]. These recent findings showed that dairy consumption contributes to 63.2% of dietary calcium intake and 28.1% of total dietary zinc intake, as well as to 47.2%, 42.9% and 17.3% of the total dietary intakes of vitamin B 12 , B 2 and B 6 respectively [2].…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…The important role of dairy in ensuring nutrient intake adequacy and sufficient concentrations of nutrient status blood indices was recently reported for the population of schoolchildren examined in the present study [2,6]. These recent findings showed that dairy consumption contributes to 63.2% of dietary calcium intake and 28.1% of total dietary zinc intake, as well as to 47.2%, 42.9% and 17.3% of the total dietary intakes of vitamin B 12 , B 2 and B 6 respectively [2].…”
Section: Introductionmentioning
confidence: 64%
“…Of these 2472 children, a representative subsample of 600 children was used to examine the current research hypothesis, for which data were already available from previous analyses on B-vitamin status markers. The selected subsample of 600 children had similar characteristics with the remaining subsample of 1872 children from the total study population, since there were no statistically significant differences observed in demographic, anthropometrical and clinical indices between the two samples [6]. More information on the sampling procedures followed is presented in details elsewhere [16].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations